Mitofusion is required for MOTS‐c induced GLUT4 translocation - Khushwant S. Bhullar (Nature Portfolio, 2021)
Abstract MOTS‐c (mitochondrial ORF of the twelve S-c) is a 16-amino-acid mitochondrial peptide that has been shown to counter insulin resistance and alleviate obesity in vivo. However, the mechanisms involved in the pharmacological action of MOTS-c remain elusive. Based on the ability of MOTS-c to improve insulin resistance and promote cold adaptation, we hypothesized that MOTS-c might play a role in boosting the number of mitochondria in a cell. We found that treatment of mammalian cells with MOTS‐c increased protein levels of TFAM, COX4, and NRF1, which are markers for mitochondrial biogenesis. However, flow cytometry analysis using MitoTracker Green revealed a sharp reduction in the mitochondrial count after MOTS‐c treatment. We then anticipated possible synchronized activation of mitofusion/mitochondrial fusion by MOTS‐c following the onset of mitochondrial biogenesis. This was confirmed after a significant increase in protein levels two GTPases, OPA1, and MFN2, both vital for the fusion of mammalian mitochondria. Finally, we found that inhibition of the two GTPases by TNFα abrogated the ability of MOTS‐c to prompt GLUT4 translocation and glucose uptake. Similar results were obtained by siRNA KD of MFN2 as well. Our results reveal for the first time a pathway that links mitofusion to MOTS-c-induced GLUT4 translocation.